The Dynamics of Secularism in Indonesia - Jannah, Miftahul; Irawani, Fivi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This paper seeks to examine the nuances of secularism in Indonesia, particularly in the context of its secular education curriculum. It is evident that the allotment of time for religious instruction in schools is limited to one to two hours per week, while in universities it is restricted to two credits in the first semester. The separation of religion and state, or secularism, can facilitate the destruction of life. The research method employed is historical. The historical method is the procedure employed by historians to describe the story of the past, based on the evidence that has been left behind. The process of historical writing comprises the following steps: The historical research method comprises four stages: heuristics, criticism, interpretation and historiography. The findings of the research indicate that secularism emerged as a consequence of the dominance of the Church over the laity during the medieval period. Subsequently, a compromise was reached whereby the Church assumed responsibility for religious affairs while scholars were tasked with addressing worldly concerns. This form of secularism was subsequently disseminated across the globe, including the Islamic world, particularly towards the end of the Ottoman Empire, which was undergoing a process of decline due to the erosion of Islamic values. With the dissolution of the Ottoman Shield, Islamic countries began to experience the influence of secularism, including Indonesia, which saw its introduction to the educational sector.